2017
DOI: 10.1002/ange.201706620
|View full text |Cite
|
Sign up to set email alerts
|

A One‐Dimensional Fluidic Nanogenerator with a High Power Conversion Efficiency

Abstract: Electricity generation from flowing water has been developed for over ac entury and playsac ritical role in our lives.G enerally,h eavy and complex facilities are required for electricity generation, while using these technologies for applications that require as mall sizea nd high flexibility is difficult. Here,w ed eveloped af luidic nanogenerator fiber from an aligned carbon nanotube sheet to generate electricity from any flowing water source in the environment as well as in the human body.T he power conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 53 publications
0
15
0
3
Order By: Relevance
“…In 2007, Liu and Dai reported that the flow-induced voltage can be greatly improved by aligning the nanotubes along the flow direction [23]. In 2017, Xu et al fabricated a fluidic nanogenerator fiber with the aligned multiwalled carbon nanotube sheet (inset of Figure 6b) [22]. The device shows a power conversion efficiency of 23.3% and an excellent stability over 1,000,000 cycles.…”
Section: Flow-induced Electricity Generationmentioning
confidence: 99%
See 3 more Smart Citations
“…In 2007, Liu and Dai reported that the flow-induced voltage can be greatly improved by aligning the nanotubes along the flow direction [23]. In 2017, Xu et al fabricated a fluidic nanogenerator fiber with the aligned multiwalled carbon nanotube sheet (inset of Figure 6b) [22]. The device shows a power conversion efficiency of 23.3% and an excellent stability over 1,000,000 cycles.…”
Section: Flow-induced Electricity Generationmentioning
confidence: 99%
“…In this setup, the moving graphene is served as driving force for ion movement, while another graphene is as a reference electrode. (a) Voltage curve induced by a saturated NaCl flow at the velocity of 1.2 cm/s [22]. (b) Relationship between the voltage and the flow velocity.…”
Section: Flow-induced Electricity Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these applications, fabricated devices based on the interactions between water molecules with graphene and/or its derivatives are of considerable interest as the energy and environmental crisis grow worse in the modern world. For example, these interactions can induce the conversion of chemical energy to electric and/or mechanical energy, which is potentially profitable for various applications such as sensors, actuators, robots, switches, artificial muscles, and electricity generators . Benefiting from the large available surface area, the unique electrical, thermal, and mechanical properties of graphene and/or its derivatives, as well as the ease of structure functionalization, device‐oriented applications based on the interactions between graphene materials and water molecules have become of increasing concern .…”
Section: Introductionmentioning
confidence: 99%